2006
DOI: 10.1142/s0218625x06008153
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF Bi SURFACTANT IN THE HETEROEPITAXIAL GROWTH OF Co ON Cu SURFACES

Abstract: We have investigated the effect of Bi on the heteroepitaxial growth of Co on Cu by reflection high-energy electron diffraction (RHEED) measurements. It was found that Bi enhanced the layer-by-layer growth of Co on the Cu (111) surfaces at 100°C. The dependence of the growth on Bi layer thickness suggested that there existed a suitable amount of Bi surfactant layer that enhanced smoother layered growth. On the contrary, for the case of Co growth on Cu (100), Bi depressed the layer-by-layer growth of Co on Cu (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Several other surfactant elements such as Bi, [26][27][28][29][30] Ag, [31][32][33][34][35] Au 36 and In 37 have been similarly found to induce layer quality improvement for physically deposited multilayers.…”
Section: D332mentioning
confidence: 99%
See 1 more Smart Citation
“…Several other surfactant elements such as Bi, [26][27][28][29][30] Ag, [31][32][33][34][35] Au 36 and In 37 have been similarly found to induce layer quality improvement for physically deposited multilayers.…”
Section: D332mentioning
confidence: 99%
“…Further studies [23][24][25][26][27] have also demonstrated the beneficial effect of Pb as surfactant in evaporated and MBE-grown FM/NM multilayers. Several other surfactant elements such as Bi, [26][27][28][29][30] Ag, [31][32][33][34][35] Au 36 and In 37 have been similarly found to induce layer quality improvement for physically deposited multilayers.…”
mentioning
confidence: 99%
“…This indicated that the growth mode as LbL growth (details are shown in Ref. [17]). When Co was deposited on Cu(100) covered with Bi atoms, the number of oscillations was decreased with increasing the deposited amount of Bi.…”
Section: Surfactant-mediated Heteroepitaxial Growth Of Co On the Cu S...mentioning
confidence: 83%
“…This indicated that the growth mode as LbL growth (details are shown in Ref. [3]). When Co was deposited on Cu(1 0 0) covered with Bi atoms, the number of oscillations was decreased with increasing the deposited amount of Bi.…”
mentioning
confidence: 83%